(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Poisoning is a common method of suicide and homicide in India, and it is associated with high mortality and morbidity. Forensic science labs have high volume of cases, leading to longer reporting times. Similarly clinical toxicology labs are either few or inadequately equipped. Therefore, it is essential to know how to start a toxicology lab. Setting up a toxicology lab requires proper planning. This includes understanding the purpose, establishing the workflow, selecting the necessary equipment and reagents, designing the layout, recruiting personnel, estimating the budget of the project and maintaining sustain ability and quality control of the lab. A toxicology lab has both clinical as well as forensic use. A careful choice must be made at each step in planning and designing depending upon the workload of cases in the chosen area of setup which can be an independent lab or part of hospital or a university or college.